Stress evaluation of different implant lengths on atrophic edentulous mandibles with fixed full-arch implant-supported prosthesis: a finite element analysis. Issue 4 (29th June 2020) - Benevides, Fernanda; Cimões, Renata; Vajgel, André; Wilmersdorf, Ramiro Brito; Vajgel, Bruna de Carvalho Farias
Abstract: Finite element analysis was used to compare the effect of different implant lengths on atrophic mandible with full-arch fixed prostheses. Four models were constructed with different implant lengths: 4, 6, 8 and 10 mm. A 100-N occlusal load was applied. The stress at the bone level, implant, and prosthetic components were obtained. Similar behavior was observed for all groups, except for 4 mm, which showed more discrepant values ​​for all prosthetic components. Although longer implants presented better biomechanical behavior, the 4 mm implant seems to be a viable alternative for severely atrophic mandibles, however, further studies need to be carried out.